Disentangling Perjury and Lying - Douglis, Allison (2018)
Committing perjury is frequently treated as closely related-if not equivalent-to lying. Both legal scholars of perjury and philosophers of lying make this assumption. This, in turn, informs subsequent conclusions about both the nature of perjury and the nature of lying